A FRANCIA SAJTÓ A TRIANONI BÉKESZERZŐDÉS ALÁÍRÁSÁRÓL: - - dr. Majoros, István - (Közép-Európai Közlemények, 2020)
The study presents the correspondence and opinion of some French newspapers about the signature of the peace treaty of Trianon. All the newspapers in France has wrote about this event and we find the reports ont he first page, sometimes with a photo. The French press presents the ceremony, the Hungarian delegates and in some lines the report presents the opinion of the journal about the peace treaty. And this opinion is negative about Hungary. The presented papers: Journal des Débats, Le Petit Parisien, Le Petit Journal, Le Matin, L’Humanité, L’Action Française.